Two Successive Type II Radio Bursts Associated With B-Class Flares and Slow CMEs - Ma, Suli; Chen, Huadong (Frontiers in Astronomy and Space Sciences, 2020)
From 2018 Oct 12 to 13, three successive solar eruptions (E1–E3) with B-class flares and poor white light coronal mass ejections (CMEs) occurred from the same active region NOAA AR 12724. Interestingly, the first two eruptions are associated with Type II radio bursts but the third is not. Using the soft X-ray flux data, radio dynamic spectra and dual perspective EUV intensity images, we comparatively investigate the three events. Our results show that their relevant flares are weak (B2.1, B7.9, and B2.3) and short-lived (13, 9, and 14 min). The main eruption directions of E1 and E2 are along 45° north of their radial directions, while E3 primarily propagated along the radial direction. In the EUV channels, the early speeds of the first two CMEs have apparent speeds of 320 and 380 km s−1, which could exceed their respective local Alfvén speeds of 300 and 350 km s−1. However, the CME in the third eruption possesses a much lower speed of 160 km s−1. These results suggest that the observed Type II radio bursts in the eruptions E1 and E2 are likely triggered by their associated CMEs and the direction of eruption and the ambient plasma and magnetic environments may take an important place in producing Type II radio burst or shock as well.